Exploring Macro BIM for Cost Prediction: Leveraging Similarity Assessment Methods and Market Data - PACYNO Hanna; JUSZCZYK Michał (Architecture, Civil Engineering, Environment)
BIM Technology allows for multidirectional analyses using the information models of building facilities. One of the areas where it is used is cost calculations, which fall under the so-called BIM 5D. This article explores the Macro BIM concept, which varies in interpretation according to literature, and its practical application. It discusses using Macro BIM model data alongside market construction data to simulate estimating building construction costs. The aim of the article is to simulate the process of calculating the estimated costs of building construction, according to the proposed course of finding the most similar objects already built to the one that is planned and calculating the unknown sought on the basis of known “reference” data. Creating a database linking market costs with building characteristics would facilitate a classification system for such surveyed buildings. Finding the most similar “reference objects” to the studied “sample” object would allow for quick, preliminary cost calculations based on the cost per unit of volume or area of the designed building. The results obtained in this preliminary study are satisfactory and have provided insight into future directions that require more detailed examination.